Public Agency Capabilities and Transformational Challenges of the 21st Century - Richard Sturn (Wirtschaftsdienst)
Abstract Combining economic theories of state and market failure with insights from other disciplines, a framework for addressing the kind of intertwined state/market failure characteristic for eras of major socioeconomic transformations is introduced. Under transformational challenges, the agency capacity of public sector is under stress due to a combination of two specific factors: (a) new coordination problems and social dilemmas, inter alia requiring changing degrees of centralisation of collective agency in a world of polycentric governance and (b) shifting rent potentials, which pre-empt public agency by multiplying situations where private agents have the means and the incentives to invest in rentenhancing and distortive rule setting (shadow politics). Coping with those challenges is a necessary condition for forwardlooking public policies.